Evaluasi Kinerja Bisnis Berbasis Business Intelligence Dashboard Pada UD. Sentral - Halim, Daniel Lexandrosth; Calim, Nicholas; Tamalate, Audrey; Felicia, Winnie (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to evaluate the effectiveness of implementing a Business Intelligence (BI) Dashboard in supporting the business performance evaluation process at UD. Sentral, a trading company engaged in the distribution of data cards and voucher products. The main issues identified include manual data recording and reporting processes that are time-consuming, prone to errors, and lack informative visualizations for management. A qualitative approach was used through interviews and direct observation with the business owner and operational staff to identify user needs and challenges. Operational data were then processed and visualized using Power BI in the form of a dashboard displaying Key Performance Indicators (KPIs), such as total sales, stock movement, customer count, and monthly sales trends. The implementation results showed that the BI dashboard improved business monitoring efficiency, accelerated evaluation processes, and supported strategic data-driven decision-making. Furthermore, the dashboard encouraged a data-driven culture and enabled early identification of declining business performance. These findings contribute to the development of data-based information systems for MSMEs in Indonesia.